A review on the applications of programmable logic controllers (PLCs) - Alphonsus, Ephrem Ryan; Mohammad Omar, Abdullah (Elsevier, 2016)
As the need of automation increases significantly, a control system needs to be easily programmable, flexible, reliable, robust and cost effective. In this paper a review on the application of programmable logic controller (PLC) in our current market is discussed. Investigations on the applications of PLCs in energy research, engineering studies, industrial control applications and monitoring of plants are reviewed in this paper. PLCs do have its own limitations, but findings indicate that PLCs have more advantages than limitations. This paper concludes that PLCs can be used for any applications whether it is of simple or complicated control system